Semantik Prosodi Nomina Indonesia dalam Korpus Wacana Berita Arab Internasional Oman 2013 - Ilfia Rahmi Rasyid; Hanady Martha Laura; Fazlur Rachman (Universitas Al Azhar Indonesia, 2022)
The prosodic semantic analysis in this research focuses on the aura of the lexical and contextual meaning of words that collocate with the noun 'Indonesia', in the international news corpus of Omani Arabic